2004
DOI: 10.1007/s11082-004-2032-9
|View full text |Cite
|
Sign up to set email alerts
|

Chirped optical pulse propagation in saturating nonlinear media

Abstract: Using a variational method, we have investigated the propagation characteristics of a chirped optical pulse in anomalously dispersive media possessing saturating nonlinearity. For the special case of uniform loss less media, the dynamics of the temporal width of the pulse is shown to be equivalent to an oscillator of unit mass which is executing its motion under some effective potential well. The potential is examined and four different types of behavior of the pulse width are noticed. The role of saturation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We consider propagation of an intense pulse in optical waveguide and model the evolution of pulse envelope (ψ(z, τ )) by the derivative non-linear Schrödinger equation [9][10][11][12]22]…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider propagation of an intense pulse in optical waveguide and model the evolution of pulse envelope (ψ(z, τ )) by the derivative non-linear Schrödinger equation [9][10][11][12]22]…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The existance of chirped solitary wave solution has been investigated by Triki et al [10]. Recently, Konar et al studied the characteristics of chirped solitary pulse in dispersive media with cubic saturable nonlinearity and showed that the pulse broadening can be reduced with increase of saturation limit [11]. The effect of cubic-quintic saturable nonlinearity on the fundamental bright soliton have been studied in dispersive media in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…(26), (27), (32) and (33), which implies that self-deflection will increase considerably at higher values of applied bias field. We find that the same self-deflections can be obtained at lower applied biased field and lower incident light in our configuration, which may be useful in practice.…”
Section: Self-deflection Of Steady-state Bright Spatial Solitonmentioning
confidence: 99%
“…Several different types of PR spatial solitons (quasisteady-state solitons [1][2][3][4], screening solitons [5][6][7][8][9][10], photovoltaic solitons [11][12][13][14], screening-photovoltaic solitons [15][16][17], selftrapping of incoherent beams [18,19] or white-light solitons [20,21], and holographic solitons [22,23]) based on single-photon PR effect have been investigated extensively in both theory and experiments. In addition, some other issues, such as the propagation characters of spatial solitons [24,25] and spatial solitons in saturating nonlinear media have also been presented yet [26,27]. Moreover, Castro-Camus et al presented a model of the twophoton PR effect which includes an intermediate allowed level (IL) to maintain a quantity of excited electrons from the valence band (VB) by the gating beam.…”
Section: Introductionmentioning
confidence: 99%